Labor Unions and the Distribution of Wages and Employment in South Africa - T. Paul Schultz; Germano Mwabu (Yale University, Economic Growth Center, 1997)
Labor unions are an important economic and political force in South Africa. Inequality in wage rates is among the largest in the world in South Africa, with African and white workers receiving wages that differ by a factor of five. The complex role of unions in closing and creating this wage gap is assessed in this paper. Union membership among Africa male workers is shown to be associated in 1993 with their receiving wages that are 145 percent higher than comparable nonunion workers in the bottom decile of the wage distribution, and 19 percent higher in the top decile of the wage distribution. Quantile regression estimates also indicate the returns to observed productive characteristics of workers, such as education and experience, are larger for nonunion than union workers. If the large union relative wage effect were reduced in half, we estimate employment of African youth, age 16-29, would increase by two percentage points, and their labor force participation rate would also increase substantially.
Keywords: 330; Labor Unions; Wages and Employment; South Africa